From repeat-pass to single-pass: City-scale 3D point-cloud reconstruction via InSAR-TomoSAR fusion with the Hongtu-1 multistatic SAR constellation - Yulun Wu; Heng Zhang; Jili Wang; Yunkai Deng; Ruizhe Liu; Qing Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Association of structural characteristics with immunostimulatory activity of pectic polysaccharides prepared from Tartary buckwheat sprouts by enzymatic degradation and partial acid hydrolysis - Lin Zhang; Bo Li; Xuan Gao; Mao-Qing Wang; Ya-Nan Cao; Mao-Ling Tan; Yi-Chen Hu; Liang Zou; Dan Li; Yong Deng; Jing-Wei Huang; Ding-Tao Wu (Food Research International, 2026)

A low-molecular-weight glucan from Lycium barbarum reprograms tumor-associated macrophages involving the Dectin-1/NOX2 axis to suppress hepatoma - Yanping Cai; Yunliang Chen; Chunjing Li; Hongxu Chen; Yi Ji; Shaojie Zhang; Ying Zhu; Shuiling Cao; Rui Xu; Xueqian Xie; Qi Yi; Qing Wang; et al. (Carbohydrate Polymers, 2026)

Sodium arsenite inhibits ALKBH7 increasing tRNA m22G methylation in mitochondrial respiratory chain complex-flankng to drive malignant phenotype of bladder epithelial cells - Wanyan Li; Zeyu Chen; Meiqi Deng; Shiwen Wang; Lei Zhang; Qing Zhou; Shuhua Xi (Chemico-Biological Interactions, 2026)

Decoding glomalin: Mycorrhizal hyphae-secreted glomalin-related soil protein in a zero-carbon background unveils Hsp60 homology and functional molecular architecture - Xiao-Qing Liu; Ci Deng; Li-Jun Zhou; Ying-Ning Zou; Qiang-Sheng Wu (Soil Biology and Biochemistry, 2026)

Exploiting interspecies interactions in a Corynebacterium–Shewanella co-culture improves succinic acid production - Zeng-Wan Deng; Bo Xu; Ming-Hou Li; Dong-Lai Fang; Xin-Qing Zhao; Kai Li (Bioresource Technology, 2026)

Rapid Detection of Spring Viremia of Carp Virus ( SVCV ) Using RAA ‐ CRISPR /Cas12a - Xiaoyang Li; Aoqing Zhang; Yingying Li; Yingying Wang; Hao Zheng; Defeng Zhang; Yan Ren; Xubing Mo; Yuting Deng; Junyu Luo; Meiling Yu; Bo Chen; et al. (Journal of Fish Diseases, 2026)
Spring viremia of carp virus (SVCV), that can infect cyprinoid and koi causing an acute hemorrhagic symptom, with a feature of widespread epidemic, which poses a severe threat to the global aquaculture industry. Given the absence of specific effective medicine or vaccines, the early, accurate diagnosis is critical in the disease prevention. Many SVCV detection methods have been established, but most require specialized equipment and skilled operators, which limits their field application. In this study, we established a recombinase‐mediated isothermal amplification (RAA) in conjunction with the CRISPR/Cas12a system targeting the screened conserved region of the G gene in the genome to identify SVCV. The optimal combination of the primer pairs and crRNA was screened via the fluorescence intensity. In addition, the test exhibited high sensitivity and specificity, which could detect at the limit of 1.243 × 10 1 copies/μL and show no cross‐reactivity with other common freshwater fish pathogens. Furthermore, the result could be visible by excitation of fluorophores by blue light at 39°C within 30 min. The integrated method combines the advantages of RAA and CRISPR‐based signal transduction, offering a diagnosis project in resource‐limited aquaculture environments and a field‐applicable early warning of SVCV.

Sedimentary-diagenetic characteristics and genesis of the Upper Cambrian reservoirs in the Tabei area, Tarim Basin, NW China - Jun Li; Kaibo Shi; Bo Liu; Yongsheng Ma; Yuanchong Wang; Qing He; Jiaming Deng; Xichuan Men; Xiangyu Bai; Jianhao Hua (Journal of Asian Earth Sciences, 2026)

Low-frequency deficit irrigation in a semi-arid vineyard of Xinjiang's Manas region: Effects on grape and wine aroma composition across three vintages - Ning Shi; Meng-Bo Tian; Hao-Cheng Lu; Yi-Fan Zhao; Ming-Yu Li; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Zhen-Zhen Zhang; Keji Yu; Yi-Bin Lan; Fei He; et al. (Food Research International, 2026)

Folic acid alleviates heat stress-induced ovarian dysfunction in dairy cows via modulation of follicular fluid metabolism and ABC transporter activity - Yaochang Wei; Yifan Yang; Yifan Li; Zhuangsheng Wang; Tingting Deng; Xiaojiao Hu; Xuefeng Jiang; Rui Xiao; Yanfang Wu; Suzhu Qing; Yongsheng Wang (Animal Reproduction Science, 2026)

Energy utilization enhancement of pulsed waterjets based on a correction of frequency equation for the ultrasonic nozzle - Juan Liu; Jingrun Cai; Xiaohui Xiao; Yong Kang; Deng Li; Xiaoqing Deng; Qing Li (Ocean Engineering, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

The real-world safety of ruxolitinib in graft-versus-host disease treatment: a pharmacovigilance study based on the FDA adverse event reporting system - Yuan-yuan Li; Wen-long Xie; Yang Zhao; Deng-zheng Zhang; Bing Mao; Qing Zhou; Yong-ji Lai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

EasyAphid: a comprehensive method for aphid infestation quantification in wheat using EVC-YOLO-Seg model and RGB images - Haotian Deng; Hui Deng; Jiawei Chen; Xin Liu; Zijun Pei; Chenzhao Gao; Qi Sun; Xin Zhang; Shijie Zhai; Xueli Hu; Shuming Fan; Xiao Wang; et al. (Computers and Electronics in Agriculture, 2026)

Integrating digital PCR and metagenomics to quantify potential soilborne bacterial pathogens in urban ecosystem - Tong Li; Kai Feng; Shang Wang; Xiongfeng Du; Jingjing Li; Songsong Gu; Bo Zhao; Xingsheng Yang; Xi Peng; Qing He; Yingcheng Wang; Danrui Wang; et al. (Journal of Hazardous Materials, 2026)

In vitro and in vivo evaluation of Bacillus amyloliquefaciens E35 as prophylactic agents against Singapore grouper iridovirus - Yanxia Gao; Lingling Deng; Yibing Wang; Lin Huang; Jieying Yu; Xiangmou Qin; Junxiang Lai; Ermeng Yu; Shuyuan Zhang; Ying Pan; Jiwei Xu; Qing Yu; et al. (Fish & Shellfish Immunology, 2026)

Impact of tropical cyclone intensity evolution under different tracks on ozone in the Pearl River Delta, China - Shanshan Ouyang; Tao Deng; Chunhui Li; Jingyang Chen; Guowen He; Xue Zhang; Qing Wang; Zebiao Zhang; Gongke Rao (Atmospheric Research, 2026)

Diversity and geographic distribution of antibiotic resistance in food waste anaerobic digestion systems - Hassan Waseem; Kai Feng; Bo Zhao; Xingsheng Yang; Mingqian Liu; Jie Wang; Jiaying Li; Qing He; Shang Wang; Yanjuan Lu; Banu Örmeci; Ye Deng (Journal of Hazardous Materials, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Advances in ecotoxicological research using planarians: a comprehensive review - Shouhui Pan; Chongtao Guo; Hai Zhang; Hao Cen; Quan Zhang; Fei Dai; Congyong Li; Qing Yang; Zhouqiong Zhang; Wang Yin; Renju Deng (Environmental Science and Pollution Research, 2026)

A semi-supervised deep learning framework based on multi-source data for wheat: from counting to yield estimation - Qing Geng; Xin Xu; Xinming Ma; Fan Xu; Jiayue Yu; Xiaoqiang Yang; Yupeng Deng; Diyou Liu; Li Li; Bingbo Gao; Yu Meng; Jianyu Yang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Synergistic catalysis of cellulose acetate-poly(ionic liquid) composite catalysts toward CO2 cycloaddition reaction - Qing Yang; Yanmei Deng; Shuangjiang Li; Xiliang Li; Tingyan Ye; Yi Liu; Yunfei Zhi; Shaoyun Shan (Journal of Environmental Chemical Engineering, 2026)

Deep eutectic solvent-based ultrasonic-assisted extraction of polyphenols from Macadamia integrifolia green peel: COSMO-RS screening, process optimization, and its application in chitosan/polyvinyl alcohol films - Ming Zhang; Yang Yang; Jian Qiao; Ya Li; Ran Kong; Jianfei Kuang; Lingdong Li; Changbin Wei; Xu Deng; Li-qing Du; Xixiang Shuai (Food Chemistry, 2026)

A wholly coherent wireless energy storage and sensing microsystem toward flexible wearable electronics - Qing You; Chang Gao; Mingjian Pan; Tongkun Wei; Weihe Shen; Xuan Yao; Hanyu Wang; Yuning Li; Xue Li; Jingye Sun; Mingqiang Zhu; Tao Deng (Chemical Engineering Journal, 2026)

An efficient 3D morphological analysis framework for pedestrian-level thermal stress assessment in megacities: Integrating large-scale modeling and physical simulation - Qipeng Deng; Gengyuan Liu; Ni Xue; Weicen Chang; Zhi Li; Qing Yang; Sana Sohail; Meirong Su (Sustainable Cities and Society, 2026)

Methanobrevibacter smithii induces postnatal growth retardation through blunting hepatic ketone body metabolism - Ming Qi; Tongxing Song; Yuankun Deng; Na Li; Nan Wang; Andong Zha; Qing Ye; Chengming Wang; Yirui Shao; Yucheng Zhu; Ming Sun; Jens Walter; et al. (Science Bulletin, 2026)

Multi-stage study of pyrolysis kinetics, combustion characteristics, and fire modeling for selected nature wood species - Yi-Xuan Lin; Qiang Wang; Qi-Xian Li; Qing-Wen Lin; Peng-Rui Man; Shu-Nan Zhou; Yang Li; Jun Deng (Fuel, 2026)

Dynamic light exposure from afternoon shading reveals aromatic plasticity in grapes and wines from a semi-arid region - Meng-Bo Tian; Ning Shi; Hao-Cheng Lu; Ming-Yu Li; Jia-Yan Wei; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Fei He; Yi-Bin Lan; Chang-Qing Duan; Keji Yu; et al. (Food Chemistry, 2026)

Metagenomics reveals potential antimicrobial peptides in Chinese baijiu fermentation - Rubing Du; Xue Li; Yan Xu; Kexin Jing; Ling Ao; Bo Deng; Qing Xu; Ping Song; Jing Yu (Food Microbiology, 2026)

Corrigendum to “Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus” [Fish Shellfish Immunol. 165 (2025) 110566] - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2026)

Traditional cupping-inspired sampling of skin interstitial fluid combined with gold nanobipyramids for multicolor visual detection of miRNAs - Qing Xiong; Chuxiang Hu; Siqi Li; Lisong Pang; Benson K. Kosgei; Xiaoyu Deng; Zhixin Li; Ray P.S. Han; Yingzhou Tao; Shaohua Xu (Chemical Engineering Journal, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Effects of As3+ stress on Pseudanabaena sp. and exploration of its enrichment mechanism through metabolomics and transcriptomics analysis - Qing Qiao; Xiaoyu Li; Jun Shi; Huiping Deng; Hairun Pei (Journal of Environmental Chemical Engineering, 2026)

A novel polyphenol-metal chelation-based structure enabling epoxy with outstanding flame retardancy, toughening effect, smoke suppression performance and recyclability - Yao Deng; Hang-Ping Fang; Qing-Qing Bi; Ying-Ming Li; De-Yi Wang (Chemical Engineering Journal, 2026)

Retraction Note to: Downregulation of the Long Non-Coding RNA Meg3 Promotes Angiogenesis After Ischemic Brain Injury by Activating Notch Signaling - Juan Liu; Qing Li; Kun-shan Zhang; Bin Hu; Xin Niu; Shu-min Zhou; Si-guang Li; Yu-ping Luo; Yang Wang; Zhi-feng Deng (Molecular Neurobiology, 2026)

Dual-Response Fluorescent Probe for HOCl and Viscosity and Cell Imaging Application - Nuo Li; Hongzhu Gou; Qingyu Deng; Qiuhong Cheng; Qing Wang; Lijuan Liang; Kun Huang (Journal of Fluorescence, 2025)

Analysis of the time-varying reliability of earth dam slopes considering multiparameter spatial variability - Zhi-Ping Deng; Yi Zou; Wenqi Du; Dian-Qing Li; Mao-Xin Wang; Shui-Hua Jiang (Computers and Geotechnics, 2025)

A flexible bionic bimodal sensor with distinguishing temperature and humidity signals - Xuan Yao; Chang Gao; Mingjian Pan; Tongkun Wei; Weihe Shen; Qing You; Hanyu Wang; Jingru Peng; Danke Chen; Xiaoqiu Tang; Xue Li; Yuning Li; et al. (Chemical Engineering Journal, 2025)

Self-adaptive S vacancy in Cu-doped ZnIn2S4 nanosheets for high-rate and ultra-stable sodium-ion battery - Zihao Li; Liuyuan Ma; Hongyou Deng; Haocun Ba; Qing Zhang; Shaozhuan Huang (Chemical Engineering Journal, 2025)

Discovery of highly effective antiviral agents based on flavonoid-benzothiazole against TMV - Jiao Tian; Chunmei Hu; Tianyu Deng; Qing Zhou; Xingping Luo; Jieyu Li; Haotao Pu; Ying Yang; Da Liu; Wei Xue (Molecular Diversity, 2025)

Study on hydrodynamic characteristics and power generation performance of FPV with a pneumatic breakwater - Peng Li; Penghao Zhang; Qing Wang; Xinyu Han; Zhongbo Deng; Xiaohui Ren; Longrui Fan; Jun Wang; Lei Wang; Yijie Huang (Ocean Engineering, 2025)

Probiotic Lactobacillus rhamnosus alleviates microcystin-LR induced visual system defects and dysfunction in zebrafish by modulating apoptosis, retinal inflammation, and phototransduction - Ning Luan; Qing Yang; Ming Liu; Ping Deng; Tien-Chieh Hung; Qin Wu; Junli Zuo; Haoling Liu; Guangyu Li (Journal of Environmental Sciences, 2025)

Structural identification and physiological function evaluation of A new natural non-protein amino acid in Camellia ptilophylla - Kaixing Fang; Minghang Xu; Dandan Qin; Hongjian Li; Erdong Ni; Bo Li; Qing Wang; Qiushuang Wang; Chendong Pan; Shulin Deng; Shengxiang Qiu; Hualing Wu (Food Chemistry, 2025)

Regulating the charge transport ability of the TiO2/CsPbI2Br perovskite interface layer by MoS2 nanoparticles for high-performance carbon-based all-inorganic perovskite solar cells - Zhaowei Huang; Lin Gao; Fengli Liu; Shihui Xu; Yaxuan Chai; Jing Li; Qing Yao; Haozhen Deng; Liuxue Sun; Jihuai Wu; Zhang Lan (Chemical Engineering Journal, 2025)

Proton exchange membranes with oriented ion channels for enhanced conductivity - Bingru Lu; Hongyang Ma; Zhanfeng Deng; Jun Lin; Zhongrui Lu; Tianxu Jin; Shaoxiong Zhai; Jiahua Li; Peng Sheng; Qing Ye; Hui Jin (Chemical Engineering Journal, 2025)

Chrysin Attenuates Myocardial Cell Apoptosis in Mice - Gang Deng; Yongzheng Yang; Ouyang Qing; Jiang Linhui; Su Haotao; Chi Liu; Ge Li; Moussa Ide Nasser (Cardiovascular Toxicology, 2025)

Flavoromics analysis and sensory evaluation of wines produced from nine red grape cultivars in Manas region, Xinjiang, China: Implications for terroir adaptation - Ning Shi; Yi-Fan Zhao; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Jia-Yi Deng; Jia-Yan Wei; Ai-Sai Chen; Chi-Fang Cheng; Shu-De Li; Fei He; Keji Yu; et al. (Food Chemistry, 2025)

Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2025)

Associations of urinary biomarkers of exposure to drinking-water disinfection by-products with haematological parameters and systemic inflammation indices among women undergoing assisted reproductive technology treatment - A-Xue Liu; Yu Miao; Min Zhang; Xiao-Ying Liu; Yan-Ling Deng; Jia-Yue Zeng; Yang-Juan Li; Wen-Qing Lu; Chang-Jiang Liu; Qiang Zeng (Environmental Pollution, 2025)

Three new aliphatic compounds from the roots of Saposhnikovia divaricata and their antiproliferative activity on HepG2 cells - Yan Liu; Jin-Hong Xue; Yan Sun; Fan-Ying Deng; Si-Yi Wang; Juan Pan; Zhi-Chao Hao; Ke-Zhen Chen; Anam Naseem; Qing-Shan Chen; Li-Li Zhang; Hai-Xue Kuang; et al. (Natural Product Research, 2025)

Applying stacked machine learning models to guide electrochemical oxidation of antibiotics: Key parameter identification and process optimization insights - Shichang Jia; Min Deng; Yue Mu; Jiahang Li; Xiaosong Tian; Qing Xie; Jinzhong Zhang (Journal of Environmental Management, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Flavobacterium aestuarii sp. nov., a novel species isolated from the Pearl River Estuary - Qi Li; Zi-Qi Peng; Hong-Chuan Wang; Lei Dong; Dan-Yuan Guo; Pan-Deng Wang; Xiao-Qing Luo; Zhen-Hao Luo; Zi-Wen Yang; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Valorization of marine crustacean shells waste via fermentation technology: A comprehensive review on derived value-added compounds and enhancing their industrial applications - Samad Tavakoli; Qing Li; Wenyu Han; Huijuan Zhang; Ma Hui; Luming Deng; Armin Mirzapour Kouhdasht; Yuqing Tan; Yongkang Luo; Hui Hong; Kefeng Wu (Waste Management, 2025)

Identification of key feature variables and prediction of harmful algal blooms in a water diversion lake based on interpretable machine learning - Yundong Wu; Bo Xian; Xiaowei Xiang; Fang Fang; Fuhao Chu; Xingkang Deng; Qing Hu; Xiuqiong Sun; Wei Tang; Shaopan Bao; Genbao Li; Tao Fang (Environmental Research, 2025)

An efficient three-dimensional mesh quality optimization method based on gradient-enhanced probabilistic model - Longwei Deng; Junhui Yin; Qing He; Xinyu Cao; Chaoyang Zhang; Junhao Cui; Bin Li (Computer Physics Communications, 2025)

Impact of the actinic radiative effect of scattering aerosols on ozone vertical distribution in the Pearl River Delta, China - Tao Deng; Shanshan Ouyang; Xiaoyang Chen; Guowen He; Xue Zhang; Jeremy Cheuk-Hin Leung; Qing Wang; Zebiao Zhang; Yu Zou; Boru Mai; Li Liu; Xuejiao Deng; et al. (Atmospheric Environment, 2025)

Nintedanib abrogates patient vitreous-induced Akt activation and tube formation of human retinal microvascular endothelial cells - Qiang Li; Xiaoping Zhou; Yanhui Yang; Qing Zhang; Zhiyuan Li; Haote Han; Fang Yuan; Hongwei Deng; Hetian Lei; Yajian Duan (Tissue and Cell, 2025)

Silencing the β-glucan recognition protein enhanced the pathogenicity of Cordyceps fumosorose against Hyphantria cunea Drury larvae - Wenxuan Li; Jianyang Bai; Jundan Deng; Weikang Xu; Qing-He Zhang; Jacob D. Wickham; Mengting Wu; Longwa Zhang (Pesticide Biochemistry and Physiology, 2025)

Effect and mechanism of calcium ions on the astringency in green tea infusion and epigallocatechin gallate solution: An in vitro oral soft tribology study - Long-Jie Xu; Qing-Qing Cao; Si-Han Deng; Wen-Jiang Dong; Qian Zou; Yong-Quan Xu; Xing-Hui Li (Food Chemistry, 2025)

Probabilistic approach to determine rainfall thresholds for rainstorm-induced shallow landslides using long-term local precipitation records - Li-Ming Zhang; Qing Lü; Zi-Hao Deng; Jie Zhang (Engineering Geology, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Leukemia inhibitory factor supplementation during in vitro maturation enhances bovine oocyte maturation and somatic cloned embryo development - Heqiang Li; Baobao Zhao; Yang Li; Jingya Wang; Tingting Deng; Qi Zhou; Jieyu Wang; Xinrui Lan; Han Zhang; Suzhu Qing; Yong Zhang; Yongsheng Wang (Animal Reproduction Science, 2025)

Differentiation of Citri Reticulatae Pericarpium varieties via HPLC fingerprinting of polysaccharides combined with machine learning - Min-yong Zhong; Meng-ning Li; Wen-shu Zou; Si-qi Hu; Jiang-nan Luo; Qing-xiang Jiang; Qiu-fang Cao; Long-fei Lin; Zhi-xin Wang; Hui Li; Wen-wen Deng (Food Chemistry, 2025)

2-Mercapto-1,3,4-thiadiazole-functionalized gold nanoclusters as a comparable bactericidal nanoantibiotic to vancomycin in treating methicillin-resistant Staphylococcus aureus infections - Quan-Quan Zhuang; Jia-Xin Ma; Yi-Ming Zheng; Lin-Yan Lu; Jia-Lin Yang; Qing-Qing Chen; Xiao-Li Yan; Yan-Cheng Jiang; Hao-Hua Deng; Wei Chen; Gang Liu (Chemical Engineering Journal, 2025)

Petrogenesis of Ke’eryin granitic pegmatites and associated Li mineralization in the Songpan–Ganze orogenic belt, China: evidence from apatite and bulk-rock chemistry - Qing-Gao Yan; Jian-Kang Li; Deng-Hong Wang; Ze-Ying Zhu; Chao Li; Zhen-Yu Chen (Mineralium Deposita, 2025)

The Same Source of Microbes has a Divergent Assembly Trajectory Along a Hot Spring Flowing Path - Qing He; Shang Wang; Kai Feng; Weiguo Hou; Wenhui Zhang; Fangru Li; Yidi Zhang; Wanming Hai; Yuxuan Sun; Ye Deng (Molecular Ecology, 2025)
Hot spring microbial mats represent intricate biofilms that establish self‐sustaining ecosystems, hosting diverse microbial communities which facilitate a range of biochemical processes and contribute to the structural and functional complexity of these systems. While community structuring across mat depth has received substantial attention, mechanisms shaping horizontal spatial composition and functional structure of these communities remain understudied. Here, we explored the contributions of species source, local environment and species interaction to microbial community assembly processes in six microbial mat regions following a flow direction with a temperature decreasing from 73.3°C to 52.8°C. Surprisingly, we found that despite divergent community structures and potential functions across different microbial mats, large proportions of the community members (45.50%–80.29%) in the recipient mat communities originated from the same source community at the upper limit of temperature for photosynthetic life. This finding indicated that the source species were dispersed with water and subsequently filtered and shaped by local environmental factors. Furthermore, critical species with specific functional attributes played a pivotal role in community assembly by influencing potential interactions with other microorganisms. Therefore, species dispersal via water flow, environmental variables, and local species interaction jointly governed microbial assembly, elucidating assembly processes in the horizontal dimension of hot spring microbial mats and providing insights into microbial community assembly within extreme biospheres.

Targeted isolation of lignans and triterpenoids from kadsura coccinea by molecular networking and anti-RA-FLS activity - Shi-qi Liu; Qing-ling Xie; Ya-si Deng; Ling Liang; Han-wen Yuan; Bin Li; Huang-he Yu; Xing Tian; Yi-xing Qiu; Guy Paulin Kemayou Mouthe; Nuzhat Shehla; Ye Zhang; et al. (Phytochemistry, 2025)

Microstructural regulation of Ir(III) complexes for enhanced photocytotoxicity in photodynamic cancer therapy - Xiaomeng Liu; Qing Zhang; Jiaqi Li; Zhewen Deng; Senqiang Zhu; Bo Ma; Rui Liu; Hongjun Zhu (Journal of Photochemistry and Photobiology B: Biology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

The impact of Barents Sea ice in May on summer extreme high-temperature events in Yangtze River Valley - Jiaxing Leng; Zhongren Deng; Shunwu Zhou; Sadashiv Chaturvedi; Yiyu Qing; Xiaotao Zhao; Jiandong Li (Climate Dynamics, 2025)

Fabrication and characterization of lysozyme fibrils/Zein complexes for resveratrol encapsulation: Improving stability, antioxidant and antibacterial activities - Min Huang; Yuling Song; Han Wang; Hao Li; Rongmi Zhou; Qing Cao; Lijuan Dong; Gerui Ren; Di Wu; Qunfang Lei; Wenjun Fang; Dan Deng; et al. (Food Chemistry, 2025)

Integrating Ni2P crystalline-NiFeBP amorphous heterojunction nanosheets on hierarchical nickel foam for superior overall water splitting - Guang-Lan Li; Fei Deng; Tian-Ge Ma; Yu-Hui Shi; Junyan Liu; Yang Yan; Qing Mao; Junjiang Bao (Chemical Engineering Journal, 2025)

miR-451a and miR-486-5p: biomarkers for benzene-induced hematotoxicity - Yanrong Lv; Zongxin Li; Yuncong Chen; Fei Qin; Qilong Liao; Zhaorui Zhang; Qifei Deng; Qing Liu; Zihao Long; Qing Wang; Wen Chen; Yongmei Xiao; et al. (Archives of Toxicology, 2025)

Corrigendum to “Transformation of cell wall pectin profile during postharvest ripening process alters drying behavior and regulates the sugar content of dried plums” [Food Chem. 458 (2024) 140093] - Xiao-Xiao Niu; Li-Zhen Deng; Haiou Wang; Qing-Hui Wang; Ming-Qiang Xu; Suo-Bin Li; Samuel Ariyo Okaiyeto; Hong-Wei Xiao (Food Chemistry, 2025)

Phthalate exposures, blood coagulation function, and assisted reproductive technology outcomes: Results from the TREE cohort study - Chong Liu; Chang-Jiang Liu; Wen-Qu Tian; Wen Yao; Yu Miao; Min Zhang; Xiao-Qiong Yuan; Yan-Ling Deng; Wen-Qing Lu; Yu-Feng Li; Qiang Zeng (Environmental Research, 2025)

Transcriptome analysis of tilapia streptococcus agalactiae in response to baicalin - Qing-Qin Huang; Shao-Long Liu; Ji-Hui Huang; Fei Wang; Zi-Chen Zhao; Heng-Wei Deng; Chuan Lin; Wei-Liang Guo; Zhi-Hong Zhong; Jian-Long Li; Dong-Dong Zhang; Shi-Feng Wang; et al. (Genes & Genomics, 2025)

Prediction of available energy and amino acid digestibility in the Chinese paddy rice fed to growing pigs - Rui Li; Ganyi Feng; Qing Ouyang; Xianji Jiang; Gang Yang; Xiaojie Liu; Hui Tang; Mingzhou Tian; Qiang Xiang; Menglong Deng; Cimin Long; Ruilin Huang (Animal Feed Science and Technology, 2025)

Enhanced degradation of polyethylene terephthalate (PET) microplastics by an engineered Stenotrophomonas pavanii in the presence of biofilm - Qing-Song Huang; Si-Qi Chen; Xiao-Min Zhao; Li-Jun Song; Yu-Ming Deng; Ke-Wei Xu; Zheng-Fei Yan; Jing Wu (Science of The Total Environment, 2024)

Mode of action underlying toxicity of Camptothecin to Spodoptera frugiperda (Lepidoptera) larvae - Jun-li Lv; Wen-qing Lai; Lei Pang; Xiao-ying Zhang; Kai-yi Zheng; Qiang Zhang; Zhan-peng Lu; Zhi-sheng Wang; Fasihul Lisan; Xue-yang Wang; Lu-feng Hu; Ming-jie Deng (Journal of Asia-Pacific Entomology, 2024)

Combined effects of benzene, toluene, xylene, ethylbenzene, and styrene exposure on hearing loss mediated by oxidative stress at realistic low levels - Yan Liu; Zihao Long; Jingjing Qiu; Qingfei Chen; Aichu Yang; Minghui Xiao; Shanfeng Dang; Yanqun Zhu; Qing Liu; Yanrong Lv; Shuangqi Li; Jingyao Qin; et al. (Environmental Pollution, 2024)

Machine learning phenotyping and GWAS reveal genetic basis of Cd tolerance and absorption in jute - Zemao Yang; Alei Li; Jiquan Chen; Zhigang Dai; Jianguang Su; Canhui Deng; Gaoao Ye; Chaohua Cheng; Qing Tang; Xiaoyu Zhang; Ying Xu; Xiaojun Chen; et al. (Environmental Pollution, 2024)

Rational design of hierarchical defect-rich NiSe2/Se-NiCuOx heterostructures: Modulating electronic structure for exceptional ammonia oxidation performance - Guang-Lan Li; Tian-Ge Ma; Yu-Hui Shi; Fei Deng; Ri-Yang Huang; Yang Yan; Qing Mao; Yushan Li; Yonghou Xiao (Chemical Engineering Journal, 2024)

Achieving nitrite shunt using in-situ free ammonia enriched by natural zeolite: Pilot-scale mainstream anammox with flexible nitritation strategy - Yongxing Chen; Chuchu Zhang; Zhenguo Chen; Zexi Deng; Qihan Wang; Qing Zou; Jiayi Li; Yu Zhang; Xiaojun Wang (Water Research, 2024)

Transformation of cell wall pectin profile during postharvest ripening process alters drying behavior and regulates the sugar content of dried plums - Xiao-Xiao Niu; Li-Zhen Deng; Haiou Wang; Qing-Hui Wang; Ming-Qiang Xu; Suo-Bin Li; Samuel Ariyo Okaiyeto; Hong-Wei Xiao (Food Chemistry, 2024)

Dielectric screening modulating charge carrier recombination in high-performance of CsPbI2Br carbon-based perovskite solar cells - Fengli Liu; Yuan Xu; Ruoshui Li; Chunyan Deng; Lin Gao; Haozhen Deng; Yu Jing; Dongbin Jiang; Qing Yao; Chenfang Zhong; Deng Wang; Jihuai Wu; et al. (Chemical Engineering Journal, 2024)

Improving broadband absorption of carbon dot conjugated melanin via pre-doping strategy as interfacial photothermal evaporator - Guoyu Kan; Yukong Li; Qing Chang; Xiaoyong Deng; Yijun Xie (Chemical Engineering Journal, 2024)

Arsenic activated GLUT1-mTORC1/HIF-1α-PKM2 positive feedback networks promote proliferation and migration of bladder epithelial cells - Zhushan Fu; Meiqi Deng; Qing Zhou; Sihao Li; Weijue Liu; Siyan Cao; Lei Zhang; Yu Deng; Shuhua Xi (Science of The Total Environment, 2024)

Complete recovery of rare earths from waste LYSO crystals by thermal shock treatment and reinforcement decomposition - Xi Zhong; Jialin Qing; Sidan Deng; Jiawei Du; Li Zeng; Qinggang Li; Guiqing Zhang; Shengxi Wu (Journal of Environmental Chemical Engineering, 2024)

Associations of occupational exposure to micro-LiNiCoMnO2 particles with systemic inflammation and cardiac dysfunction in cathode material production for lithium batteries - Yaotang Deng; Guoliang Li; Lijie Xie; Xiaoliang Li; Youyi Wu; Jiewei Zheng; Simin Xian; Jiazhen Zhou; Jiabin Chen; Yuewei Liu; Qiaoyuan Yang; Qing Wang; et al. (Environmental Pollution, 2024)

Effects of cadmium on the intestinal health of the snail Bradybaena ravida Benson - Yan-Mei Da; Shun-Shun Li; Yan-Qi Li; Le-Yu Deng; Ming-Jun Li; Tao Huang; Qing-Ye Sun; Jazbia Shirin; Guo-Wei Zhou (Ecotoxicology, 2024)

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Impact of aerosol actinic radiative effect on ozone during haze pollution in the Pearl River Delta region - Tao Deng; Shanshan Ouyang; Guowen He; Xue Zhang; Jeremy Cheuk-Hin Leung; Xiaoyang Chen; Qing Wang; Zebiao Zhang; Yu Zou; Boru Mai; Li Liu; Xuejiao Deng (Atmospheric Environment, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Early-onset and later-onset cancer: trends, risk factors, and prevention in Northern China - Tong Liu; Chen-An Liu; Qing-Song Zhang; Qi Zhang; Yi-Ming Wang; Meng-Meng Song; Shi-Qi Lin; Li Deng; Shou-Ling Wu; Han-Ping Shi (Science China Life Sciences, 2024)

Triggering Receptor Expressed on Myeloid Cells 2 Alleviated Sevoflurane-Induced Developmental Neurotoxicity via Microglial Pruning of Dendritic Spines in the CA1 Region of the Hippocampus - Li Deng; Shao-Yong Song; Wei-Ming Zhao; Xiao-Wen Meng; Hong Liu; Qing Zheng; Ke Peng; Fu-Hai Ji (Neuroscience Bulletin, 2024)

A new method for predicting precipitation δ 18 O distribution based on deep learning and spatio-temporal clustering - Yang Li; Siyuan Huo; Bin Ma; Bingbing Pei; Qiankun Tan; Qing Guo; Deng Wang; Longbiao Yu (Hydrological Sciences Journal, 2024)

Integrated analysis of the gonadal methylome and transcriptome provides new insights into the expression regulation of sex determination and differentiation genes in spotted scat (Scatophagus argus) - Kai-Zhi Jiao; Yu Li; Yuan-Qing Huang; Charles Brighton Ndandala; Gang Shi; Si-Ping Deng; Hong-Juan Shi; Hua-Pu Chen; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2024)

Deciphering the pathogenic risks of microplastics as emerging particulate organic matter in aquatic ecosystem - Ling-Zi Yin; Xiao-Qing Luo; Jia-Ling Li; Zetao Liu; Li Duan; Qi-Qi Deng; Chen Chen; Shaojun Tang; Wen-Jun Li; Pandeng Wang (Journal of Hazardous Materials, 2024)

Stability of tryptophan-containing LOs in flaxseed oil and their response towards γ-tocopherol - Wan-zhen Li; Zi-liang Song; Jun-le Li; Jia-hui Yu; Du-jian Deng; Xiao-qing Cai; Martin J.T. Reaney; Zi-zhe Cai; Yong Wang (Food Chemistry, 2024)

Fe/Co bimetallic nanozyme disrupting tumorous Self-Regulatory pathways to potentiate ferroptosis - Qing Liu; Qian Chen; Xi Deng; Yutong Zhu; Zhangpeng Shi; Runjie Miao; Ming Ma; Nian Ran; Cheng Li; Hangrong Chen (Chemical Engineering Journal, 2024)

Electrocatalytic nitrogen reduction to ammonia at low overpotentials based on tungsten carbide doped by non-precious metal single cobalt atoms - Ya Gao; Meng-Jiao Zhu; Xian-He Liu; Guo-Liang Dai; Yi-Wen Zhou; Ze-Da Meng; Li Luo; Tian Gan; Feng Chen; Yu-Yang Zhou; Wen-Wen Deng; Shou-Qing Liu (Chemical Engineering Journal, 2024)

Cyanidin prevents cardiomyocyte apoptosis in mice after myocardial infarction - Deng Gang; Ouyang Qing; Yongzheng Yang; Muqaddas Masood; Yu-Hong Wang; Jiang Linhui; Su Haotao; Ge Li; Chi Liu; Moussa Ide Nasser; Ping Zhu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Rapid improvement of grain appearance in three-line hybrid rice via CRISPR/Cas9 editing of grain size genes - Juan Huang; Weiwei Chen; Lijun Gao; Dongjin Qing; Yinghua Pan; Weiyong Zhou; Hao Wu; Jingcheng Li; Chonglie Ma; Changlan Zhu; Gaoxing Dai; Guofu Deng (Theoretical and Applied Genetics, 2024)
Key message Genetic editing of grain size genes quickly improves three-line hybrid rice parents to increase the appearance quality and yield of hybrid rice. Abstract Grain size affects rice yield and quality. In this study, we used CRISPR/Cas9 to edit the grain size gene GW8 in the maintainer line WaitaiB (WTB) and restorer line Guanghui998 (GH998). The new slender sterile line WTEA ( gw8 ) was obtained in the BC 2 F 1 generation by transferring the grain mutation of the maintainer plant to the corresponding sterile line WantaiA (WTA, GW8 ) in the T 1 generation. Two slender restorer lines, GH998E1 ( gw8(II) ) and GH998E2 ( gw8(I) ), were obtained in T 1 generation. In the early stage, new sterile and restorer lines in grain mutations were created by targeted editing of GS3 , TGW3 , and GW8 genes. These parental lines were mated to detect the impact of grain-type mutations on hybrid rice yield and quality. Mutations in gs3 , gw8, and tgw3 had a minimal impact on agronomic traits except the grain size and thousand-grain weight. The decrease in grain width in the combination mainly came from gw8/gw8 , gs3/gs3 increased the grain length, gs3/gs3 - gw8/gw8 had a more significant effect on the grain length, and gs3/gs3-gw8/gw8(I) contributed more to grain length than gs3/gs3-gw8/gw8(II) . The heterozygous TGW3/tgw3 may not significantly increase grain length. Electron microscopy revealed that the low-chalky slender-grain variety had a cylindrical grain shape, a uniform distribution of endosperm cells, and tightly arranged starch grains. Quantitative fluorescence analysis of endospermdevelopment-related genes showed that the combination of slender grain hybrid rice caused by gs3 and gw8 mutations promoted endosperm development and improved appearance quality. An appropriate grain size mutation resulted in hybrid rice varieties with high yield and quality.

Effects of sourdough on bread staling rate: From the perspective of starch retrogradation and gluten depolymerization - Meixuan Li; Honghong Zhang; Lingyi Lyu; Qing Deng; Haoran Fan; Xueming Xu; Dan Xu (Food Bioscience, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Dynamic causal modeling analysis reveals the modulation of motor cortex and integration in superior temporal gyrus during multisensory speech perception - Ting Zou; Liyuan Li; Xinju Huang; Chijun Deng; Xuyang Wang; Qing Gao; Huafu Chen; Rong Li (Cognitive Neurodynamics, 2024)
The processing of speech information from various sensory modalities is crucial for human communication. Both left posterior superior temporal gyrus (pSTG) and motor cortex importantly involve in the multisensory speech perception. However, the dynamic integration of primary sensory regions to pSTG and the motor cortex remain unclear. Here, we implemented a behavioral experiment of classical McGurk effect paradigm and acquired the task functional magnetic resonance imaging (fMRI) data during synchronized audiovisual syllabic perception from 63 normal adults. We conducted dynamic causal modeling (DCM) analysis to explore the cross-modal interactions among the left pSTG, left precentral gyrus (PrG), left middle superior temporal gyrus (mSTG), and left fusiform gyrus (FuG). Bayesian model selection favored a winning model that included modulations of connections to PrG (mSTG → PrG, FuG → PrG), from PrG (PrG → mSTG, PrG → FuG), and to pSTG (mSTG → pSTG, FuG → pSTG). Moreover, the coupling strength of the above connections correlated with behavioral McGurk susceptibility. In addition, significant differences were found in the coupling strength of these connections between strong and weak McGurk perceivers. Strong perceivers modulated less inhibitory visual influence, allowed less excitatory auditory information flowing into PrG, but integrated more audiovisual information in pSTG. Taken together, our findings show that the PrG and pSTG interact dynamically with primary cortices during audiovisual speech, and support the motor cortex plays a specifically functional role in modulating the gain and salience between auditory and visual modalities.

Sublethal effects of chlorantraniliprole on immunity in Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae): Promote encapsulation by upregulating a heat shock protein 70 family gene SfHSP68.1 - Wenqi Xie; Xiaoyue Deng; Wencai Tao; Zhihui Zhang; Huilai Zhang; Qing Li; Chunxian Jiang (Pesticide Biochemistry and Physiology, 2024)

Simultaneous detection of three nitrofuran antibiotics by the lateral flow immunoassay based on europium nanoparticles in aquatic products - Qing Mei; Biao Ma; Jiali Li; Xin Deng; Jiangbing Shuai; Yuxin Zhou; Mingzhou Zhang (Food Chemistry, 2024)

8-OHdG mediates the association of co-exposure to fifty-five typical endocrine-disrupting chemicals with renal function: a cross-section investigation in Southern Chinese adults - Qingfei Chen; Qifei Deng; Qilong Liao; Yan Liu; Zhaorui Zhang; Dehua Wu; Yanrong Lv; Jingyao Qin; Qing Liu; Shuangqi Li; Zihao Long; Xiumei Xing; et al. (Environmental Science and Pollution Research, 2024)

Diffusion characteristics of coal dust associated with different ventilation methods in underground excavation tunnel - Yang Xiao; Xue-Er Yang; Zhen-Ping Wang; Qing-Wei Li; Jun Deng (Process Safety and Environmental Protection, 2024)

Hazards of microplastics exposure to liver function in fishes: A systematic review and meta-analysis - Yu Sun; Qingfang Deng; Qiurong Zhang; Xin Zhou; Ruhai Chen; Siyu Li; Qing Wu; Huaguo Chen (Marine Environmental Research, 2024)

Co-exposure of petrochemical workers to noise and mixture of benzene, toluene, ethylbenzene, xylene, and styrene: Impact on mild renal impairment and interaction - Qingfei Chen; Qifei Deng; Yan Liu; Zihao Long; Shuangqi Li; Qing Liu; Yanrong Lv; Jingyao Qin; Aichu Yang; Yongshun Huang; Zhaoqing Tan; Dongsheng Wang; et al. (Environmental Pollution, 2024)

Silica nanoparticles conferring resistance to bacterial wilt in peanut (Arachis hypogaea L.) - Quanqing Deng; Suihua Huang; Hao Liu; Qing Lu; Puxuan Du; Haifen Li; Shaoxiong Li; Haiyan Liu; Runfeng Wang; Lu Huang; Dayuan Sun; Yahui Wu; et al. (Science of The Total Environment, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Evaluation of the potential of endophytic Trichoderma sp. isolated from medicinal plant Ampelopsis japonica against MRSA and bioassay-guided separation of the anti-MRSA compound - Jianbin Li; Siyun Xie; Qing Gao; Zujun Deng (Brazilian Journal of Microbiology, 2024)

Virgin coconut oil: A comprehensive review of antioxidant activity and mechanisms contributed by phenolic compounds - Yu-Qing Zeng; Jin-Tao He; Bo-Yong Hu; Wen Li; Jing Deng; Qin-Lu Lin; Yong Fang (Critical Reviews in Food Science and Nutrition, 2024)

Elucidating the mechanisms underlying astrocyte-microglia crosstalk in hippocampal neuroinflammation induced by acute diquat exposure - Changcun Qi; Yuandong Yan; Qi Cao; Lingyun Zou; Shanshan Li; Qiuyu Yang; Qing Deng; Bailin Wu; Bo Song (Environmental Science and Pollution Research, 2024)

Fruit tree canopy segmentation from UAV orthophoto maps based on a lightweight improved U-Net - Zhikai Li; Xiaoling Deng; Yubin Lan; Cunjia Liu; Jiajun Qing (Computers and Electronics in Agriculture, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Belowground C sequestrations response to grazing exclusion in global grasslands: Dynamics and mechanisms - Qing Qu; Lei Deng; Zhouping Shangguan; Jian Sun; Jinsheng He; Kaibo Wang; Zhengchao Zhou; Jiwei Li; Josep Peñuelas (Agriculture, Ecosystems & Environment, 2024)

Assessing the resilience of complex ecological spatial networks using a cascading failure model - Qing Xiang; Huan Yu; Hong Huang; Feng Li; LingFan Ju; Wenkai Hu; Peng Yu; ZongChun Deng; YanNi Chen (Journal of Cleaner Production, 2024)

Pressure–temperature–time path of ultrahigh-pressure metamorphic terranes constrained by zircon petrochronology: A case study of orthogneisses from the northern Sulu belt, China - Peng Feng; Hao Deng; Yang Zhang; Qing-Lin Sui; Hai-Yang He; Yan-Shi Xie; Liang Chen; Xian-Zhe Duan; Wen-Zhou Xiao; Xia-Wen Li; Nan Li (Journal of Asian Earth Sciences, 2024)

High-performance lithium metal batteries enabled by a nano-sized garnet solid-state electrolyte modified separator - Kai Yu; Huipeng Zeng; Jun Ma; Yidong Jiang; Huiyun Li; Ludan Zhang; Qiangqiang Zhang; Xuyi Shan; Tingting Li; Xiaoqi Wu; Hongli Xu; Wei Huang; et al. (Chemical Engineering Journal, 2024)

Variation characteristics of dust in the Taklimakan Desert - Lili Jin; Qing He; Zhenjie Li; Mingzai Deng; Alim Abbas (Natural Hazards, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Synthesis and evaluation of in vitro and in vivo anti -Toxoplasma gondii activity of tetraoxane-substituted ursolic acid derivatives - Ya-Lan Wang; Li-Li Jin; Xu Cheng; Wei-Feng Yan; Hao Deng; Qing-Kun Shen; Zhe-Shan Quan; Chun-Mei Jin; Chang-Hao Zhang (Natural Product Research, 2023)

Dust diffusion laws during partition excavation by boom-type roadheader in a metro tunnel - Ning Liu; Xiong Wu; E Deng; Yi-Qing Ni; Wei-Chao Yang; Guo-Zhi Li (Tunnelling and Underground Space Technology, 2023)

Unravelling chilling-stress resistance mechanisms in endangered Mangrove plant Lumnitzera littorea (Jack) Voigt - Xinhui Xia; Lulu Hao; Yifei Sun; Yiqing Lv; Yihong Wang; Haiyu Wu; Zongjin Jiang; Xinru Li; Yuhan Yan; Xiaojian Chen; Binghou Li; Hao Li; et al. (Marine Environmental Research, 2023)

GPT-aided diagnosis on agricultural image based on a new light YOLOPC - Jiajun Qing; Xiaoling Deng; Yubin Lan; Zhikai Li (Computers and Electronics in Agriculture, 2023)

Effect of short-term ambient air pollution exposure on early miscarriage and pregnancy hormones with critical window identification - Qing Xu; Quanquan Guan; Yingying Lu; Jie Xu; Siting Deng; Chao Dong; Xiaochen Zhang; Wen Li; Yankai Xia (Journal of Hazardous Materials, 2023)

The effect of alginate oligosaccharides on intestine barrier function and Vibrio parahaemolyticus infections in the white shrimp Litopenaeus vannamei - Nan Bai; Wanzhen Deng; Zezheng Qi; Shihui Pan; Qing Li; Min Gu (Fish & Shellfish Immunology, 2023)

Description of Xanthocytophaga agilis sp. nov. and Xanthocytophaga flavus sp. nov. of the new genus Xanthocytophaga gen. nov and the proposal of Rhodocytophagaceae fam. nov. within the order Cytophagales - Xianjiao Zhang; Guang-Da Feng; Yang Liu; Fan Yang; Yanxuan Li; Xiaoqin Deng; Honghui Zhu; Qing Yao (Archives of Microbiology, 2023)

Alsobacter ponti sp. nov., a novel denitrification and sulfate reduction bacterium isolated from Pearl River sediment - Qi-Qi Deng; Xiao-Qing Luo; Shan-Hui Li; Jia-Ling Li; Pan-Deng Wang; Yang Yuan; Zi-Wen Yang; Wen-Jun Li (Antonie van Leeuwenhoek, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Temporal framework for the Yanliao Biota and timing of the origin of crown mammals - Zhiqiang Yu; Haibing Wang; Chi Zhang; Liping Dong; Magdalena H. Huyskens; Zexian Cui; Paige Cary; Yankun Di; Yuri Amelin; Gang Li; Qiuli Li; Xiao-Ping Xia; et al. (Earth and Planetary Science Letters, 2023)

Study on the characteristics of actinic radiation and direct aerosol radiation effects in the Pearl River Delta region - Tao Deng; Yu Zou; Sheng Hu; Fei Li; Guowen He; Shanshan Ouyang; Xue Zhang; Qing Wang; Zebiao Zhang; Boru Mai; Li Liu; Luyao Zhang; et al. (Atmospheric Environment, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

Two lanostane triterpenoids with α -glucosidase inhibitory activity from the fruiting bodies of Ganoderma weberianum - De Xian Kong; Qing Yun Ma; Li Yang; Qing Yi Xie; Chun Ying Deng; Hao Fu Dai; Yan Hua; You Xing Zhao (Natural Product Research, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Phthalate exposure with sperm quality among healthy Chinese male adults: The role of sperm cellular function - Pan Yang; Lang-Jing Deng; Jin-Ying Xie; Xiao-Jie Li; Xiao-Na Wang; Bin Sun; Tian-Qing Meng; Cheng-Liang Xiong; Yi-Chao Huang; Yi-Xin Wang; An Pan; Da Chen; et al. (Environmental Pollution, 2023)

Aberrant adenosine signaling in patients with focal cortical dysplasia - Mengyi Guo; Jing Zhang; Jing Wang; Xiongfei Wang; Qing Gao; Chongyang Tang; Jiahui Deng; Zhonghua Xiong; Xiangru Kong; Yuguang Guan; Jian Zhou; Detlev Boison; et al. (Molecular Neurobiology, 2023)

Mechanism of subsidence-buckling and instability of slopes in thick-layered rigid rock under mining - Jie Deng; Jian-jun Zhao; Qi-yi Lai; Ai-nong Li; Ming-li Xie; Qing-miao Li; Xiao Zhao (Journal of Mountain Science, 2023)

Effects of defatted yellow mealworm (Tenebrio molitor) on growth performance, intestine, and liver health of turbot (Scophthalmus maximus) - Nan Bai; Qing Li; Shihui Pan; Zezheng Qi; Wanzhen Deng; Min Gu (Animal Feed Science and Technology, 2023)

Spatio-and temporal patterns of Jurassic–Early Cretaceous volcanism in the Great Xing’an range, NE China: constraints on the geodynamic evolution - Zong-Yuan Tang; Jie Li; Qing-Yang Li; De-You Sun; Jun Gou; Chang-Zhou Deng (International Geology Review, 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

Photo-aging promotes the inhibitory effect of polystyrene microplastics on microbial reductive dechlorination of a polychlorinated biphenyl mixture (Aroclor 1260) - Youhua Chen; Lingfang Ni; Qing Liu; Zhaochao Deng; Jiawei Ding; Li Zhang; Chunfang Zhang; Zhongjun Ma; Dongdong Zhang (Journal of Hazardous Materials, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Polycyclic aromatic hydrocarbons in the Chinese diet: contamination characteristics, indicator screening, and health risk assessment - Feifei Huang; Lei Zhang; Moqin Zhou; Jianwen Li; Qing Liu; Bo Wang; Ke Deng; Pingping Zhou; Yongning Wu (Food Additives & Contaminants: Part A, 2023)

Corrigendum to “Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus)” [Aquaculture 563 (2023) /739023] - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Intercropped soybean boosts nitrogen benefits and amends nitrogen use pattern under plastic film mulching in the semiarid maize field - Wei Zhang; Yong-Xian Wei; Aziz Khan; Jun-Sheng Lu; Jun-Lan Xiong; Shuang-Guo Zhu; Xiang-Wen Fang; Wei Wang; Meng Hao; Ling Zhao; Xiao-Lin Zhang; Jian-Ming Deng; et al. (Field Crops Research, 2023)

Characterization of phytopathogen-preying Hyalangium versicolor sp. nov., and proposal for the reclassification of Cystobacter gracilis as Hyalangium gracile comb. Nov - Xianjiao Zhang; Guangda Feng; Yang Liu; Jiali Li; Xiaoqin Deng; Qing Yao; Honghui Zhu (Archives of Microbiology, 2023)

Isothermal exponential amplification reactions triggered by circular templates (cEXPAR) targeting miRNA - Xue-mei Qu; Xiao-dong Ren; Ning Su; Xian-ge Sun; Shao-li Deng; Wei-ping Lu; Qing Huang (Molecular Biology Reports, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Pseudomonas citri sp. nov., a potential novel plant growth promoting bacterium isolated from rhizosphere soil of citrus - Hong Gao; Guang-Da Feng; Zengwei Feng; Qing Yao; Jiali Li; Xiaoqin Deng; Xiaoran Li; Honghui Zhu (Antonie van Leeuwenhoek, 2023)

Transcriptomic analysis provides new insights into the secondary follicle growth in spotted scat (Scatophagus argus) - Mou-Yan Jiang; Yi-Fan Zhou; Hao Liu; You-Xing Peng; Yuan-Qing Huang; Si-Ping Deng; Yang Huang; Gang Shi; Chun-Hua Zhu; Guang-Li Li; Dong-Neng Jiang (Frontiers in Marine Science, 2023)
Spotted scat ( Scatophagus argus ) is an important mariculture fish that is of great economic significance in East and Southeast Asia. To date, there are no studies on ovary development and regulation in S. argus . Herein, the ovary transcriptome profiles of S. argus at different stages were constructed, and the genes and pathways potentially involved in secondary follicle growth were identified. A total of 25,426 genes were detected by sequencing the mRNAs from the ovary libraries at stage III (n=3) and IV (n=3). Notably, 2950 and 716 genes were up-regulated and down-regulated in the stage IV ovary, respectively, compared to the stage III ovary. The differentially expressed genes (DEGs) were found to be mostly involved in regulating steroidogenesis, vitellogenesis, lipid metabolism, and meiosis. Up-regulation of steroid hormone synthesis pathway genes ( fshr , cyp17a1 , and foxl2 ) and insulin-like growth factor pathway genes ( igf1r , ifg2r , igfbp1 , igfbp3 , and igfbp7 ) in the ovary at stage IV was possibly the reason for the increased serum estrogen. Moreover, ppara , ppard , fabp3 , and lpl were up-regulated in the stage IV ovary and were potentially involved in the lipid droplet formation in the oocyte. Many DEGs were involved in the cellular cycle, meiosis, and cAMP or cGMP synthesis and hydrolysis, indicating that meiosis was restarted at stage IV ovary. In addition, numerous TGF-beta signal pathway genes were up-regulated in the stage IV ovary. This ovary transcript dataset forms a baseline for investigating functional genes associated with oogenesis in S. argus .

Low-tortuosity carbon electrode derived from Wood@ZIF-67 for supercapacitor applications - Zhen Zhang; Songlin Deng; Delong Wang; Yan Qing; Ge Yan; Lei Li; Yiqiang Wu (Chemical Engineering Journal, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus) - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Assessment of algae and greenhouse gases in different reservoirs worldwide by reactor model - Yi-Xuan Li; Kai-Kai Deng; Shu-Qing Zhang; Gui-Jiao Lin; Fang Fang; Jin-Song Guo (Journal of Cleaner Production, 2023)

Urinary phthalate metabolites and the risk of endometrial polyp: A pilot study from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Wen Yao; Qing-Yun Yao; Yong Huang; Ni-Jie Li; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Yu-Feng Li; et al. (Environmental Pollution, 2023)

In situ modulation of Pt-Ni heterocatalysts on highly graphitized wood-derived carbon platform to boost hydrogen production - Zhifei Gao; Yu Liao; Ashen Deng; Yujie Liu; Yun Wang; Liaoyuan Xia; Yan Qing; Xingong Li; Yiqiang Wu (Chemical Engineering Journal, 2023)

Relation of Carotid Plaque Features Detected with Ultrasonography-Based Radiomics to Clinical Symptoms - Zhe Huang; Xue-Qing Cheng; Hong-Yun Liu; Xiao-Jun Bi; Ya-Ni Liu; Wen-Zhi Lv; Li Xiong; You-Bin Deng (Translational Stroke Research, 2022)

Identification of a stable major-effect quantitative trait locus for pre-harvest sprouting in common wheat (Triticum aestivum L.) via high-density SNP-based genotyping - Zhi Li; Yongyan Chen; Xia Ou; Mengning Wang; Nanxin Wang; Wei Li; Yawen Deng; Yixin Diao; Zixin Sun; Qinyi Luo; Xinli Li; Liqi Zhao; et al. (Theoretical and Applied Genetics, 2022)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

Comparative transcriptome and adaptive evolution analysis on the main liver and attaching liver of Pareuchiloglanis macrotrema - Qing Wu; Xiaoyang Zhang; Jie Li; Longjun Deng; Dongjie Wang; Min Liao; Zhonggang Guo; Xiaoli Huang; Defang Chen; Yan Wang; Shiyong Yang; Zongjun Du; et al. (Journal of Applied Genetics, 2022)

46,XY disorders of sex development: the use of NGS for prevalent variants - Qi-Gen Xie; Peng Luo; Kai Xia; Zuo-Qing Li; Zhe Xu; Cheng Su; Chun-Hua Deng (Human Genetics, 2022)

Paenibacillus hamazuiensis sp. nov., a bacterium isolated from Hamazui hot spring in Yunnan province, south-west China - Juan Wang; Ming Deng; En-Min Zhou; Lei Ran; Cui-Ping Miao; Yi-Qing Li; Jun-Mei Ding; Shu-Kun Tang (Archives of Microbiology, 2022)

Will farmers follow their peers in adopting straw returning? Evidence from rural Sichuan Province, China - Yanjiao Li; Chen Qing; Shili Guo; Xin Deng; Jiahao Song; Dingde Xu (Environmental Science and Pollution Research, 2022)

Maternal exposure to cooking oil fumes during pregnancy and autistic‐like behaviors in Chinese preschoolers - Jian-Hui Yang; Esben Strodl; Chuan-An Wu; Xiang-Yu Hou; Xiao-Na Yin; Guo-Min Wen; Deng-Li Sun; Dan-Xia Xian; Jing-Yi Chen; Ying-Jie Chen; Jing Chen; Wei-Qing Chen (Environmental Science and Pollution Research, 2022)

Assessment of microbial α-diversity in one meter squared topsoil - Shuzhen Li; Xiongfeng Du; Kai Feng; Yueni Wu; Qing He; Zhujun Wang; Yangying Liu; Danrui Wang; Xi Peng; Zhaojing Zhang; Arthur Escalas; Yuanyuan Qu; et al. (Soil Ecology Letters, 2022)

Petrogenesis of Early-Middle Jurassic gabbros in southern Tibet with implications for crustal growth in the southern Lhasa subterrane - Liang Li; Hui Xie; Xinghai Lang; Xuhui Wang; Qing He; Yulin Deng; Fuwei Xie (International Geology Review, 2022)

Expanding the clinical spectrum of adult-onset neuronal intranuclear inclusion disease - Yuwen Cao; Jingying Wu; Yunhua Yue; Chao Zhang; Shihua Liu; Ping Zhong; Shige Wang; Xiaojun Huang; Weiping Deng; Jing Pan; Lan Zheng; Qing Liu; et al. (Acta Neurologica Belgica, 2022)

Xylariaopyrones E–I, five new α-pyrone derivatives from the endophytic fungus Xylariales sp. (HM-1) - Wen-Wen Yang; Li-Wen Lu; Xue-Qing Zhang; Shang-Song Bao; Fei Cao; Zhi-Yong Guo; Zhang-Shuang Deng; Peter Proksch (Natural Product Research, 2022)

Mutation of Beclin1 acetylation site at K414 alleviates high glucose-induced podocyte impairment in the early stage of diabetic nephropathy by inhibiting hyperactivated autophagy - Jun Xu; Yujie Deng; Yingying Ke; Yunxia Zhu; Ping Wang; Qing Yu; Chengqian Li; Bimin Shi (Molecular Biology Reports, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Analysis of the starch properties in tetraploid wheat–Aegilops sharonensis amphidiploid - Qing Li; Xuteng Zhang; Na Lin; Guzmán Carlos; Jingyu Lan; Huaping Tang; Pengfei Qi; Jian Ma; Jirui Wang; Guoyue Chen; Wei Li; Zhien Pu; et al. (Cereal Research Communications, 2021)

Short-term waterlogging-induced autophagy in root cells of wheat can inhibit programmed cell death - Li-Lang Zhou; Kai-Yue Gao; Li-Sha Cheng; Yue-Li Wang; Yi-Keng Cheng; Qiu-Tao Xu; Xiang-Yi Deng; Ji-Wei Li; Fang-Zhu Mei; Zhu-Qing Zhou (Protoplasma, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Galectin-9 Promotes Neuronal Restoration via Binding TLR-4 in a Rat Intracerebral Hemorrhage Model - Tianyu Liang; Cheng Ma; Tianyi Wang; Ruming Deng; Jiasheng Ding; Wenjie Wang; Zhongmou Xu; Xiang Li; Haiying Li; Qing Sun; Haitao Shen; Zhong Wang; et al. (NeuroMolecular Medicine, 2021)

Whole-genome resequencing reveals loci with allelic transmission ratio distortion in F1 chicken population - Peng Ren; Feilong Deng; Shiyi Chen; Jinshan Ran; Jingjing Li; Lingqian Yin; Yan Wang; Huadong Yin; Qing Zhu; Yiping Liu (Molecular Genetics and Genomics, 2021)

SIMS U-Pb geochronology for the Jurassic Yanliao Biota from Bawanggou section, Qinglong (northern Hebei Province, China) - Zhiqiang Yu; Huaiyu He; Gang Li; Chenglong Deng; Haibing Wang; Xinxin Zhang; Qing Yang; Xiao-Ping Xia; Zhonghe Zhou; Rixiang Zhu (International Geology Review, 2021)

Piriformospora indica colonization increases the growth, development, and herbivory resistance of sweet potato (Ipomoea batatas L.) - Qing Li; Yun-Wei Kuo; Kuan-Hung Lin; Weiqun Huang; Caisheng Deng; Kai-Wun Yeh; Shi-Peng Chen (Plant Cell Reports, 2021)

Steeper spatial scaling patterns of subsoil microbiota are shaped by deterministic assembly process - Xiongfeng Du; Ye Deng; Shuzhen Li; Arthur Escalas; Kai Feng; Qing He; Zhujun Wang; Yueni Wu; Danrui Wang; Xi Peng; Shang Wang (Molecular Ecology, 2021)
Although many studies have investigated the spatial scaling of microbial communities living in surface soils, very little is known about the patterns within deeper strata, nor is the mechanism behind them. Here, we systematically assessed spatial scaling of prokaryotic biodiversity within three different strata (Upper: 0–20 cm, Middle: 20–40 cm, and Substratum: 40–100 cm) in a typical grassland by examining both distance–decay (DDRs) and species–area relationships (SARs), taxonomically and phylogenetically, as well as community assembly processes. Each layer exhibited significant biogeographic patterns in both DDR and SAR ( p β and z values, respectively, ranged from 0.016 ± 0.005 to 0.023 ± 0.005 and 0.065 ± 0.002 to 0.077 ± 0.004 across soil strata, and both increased with depth. Moreover, the prokaryotic community in grassland soils assembled mainly according to deterministic rather than stochastic mechanisms. By using normalized stochasticity ratio (NST) based on null model, the relative importance of deterministic ratios increased from 48.0 to 63.3% from Upper to Substratum, meanwhile a phylogenetic based method revealed average βNTI also increased with depth, from −5.29 to 19.5. Using variation partitioning and distance approaches, both geographic distance and soil properties were found to strongly affect biodiversity structure, the proportions increasing with depth, but spatial distance was always the main underlying factor. These indicated increasingly deterministic proportions in accelerating turnover rates for spatial assembly of prokaryotic biodiversity. Our study provided new insights on biogeography in different strata, revealing importance of assembly patterns and mechanisms of prokaryote communities in below‐surface soils.

Construction and characterization of UAA-controlled recombinant Zika virus by genetic code expansion - Rong-Rong Zhang; Qing Ye; Xiao-Feng Li; Yong-Qiang Deng; Yan-Peng Xu; Xing-Yao Huang; Qing Xia; Cheng-Feng Qin (Science China Life Sciences, 2021)

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

Role of T-type Calcium Channels in Generating Hyperexcitatory Behaviors during Emergence from Sevoflurane Anesthesia in Neonatal Rats - Feng-Yan Shen; Byung-Gun Lim; Wen Wen; Yu Zhang; Bo Cao; Yue-Guang Si; Li-Qing Ma; Meng Deng; Yang In Kim; Young-Beom Kim; Ying-Wei Wang (Neuroscience Bulletin, 2020)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

Antifungal Susceptibility Profile of Candida Albicans Isolated from Vulvovaginal Candidiasis in Xinjiang Province of China - Liang Yan; Xiao-dong Wang; Seyedmojtaba Seyedmousavi; Juan-na Yuan; Palida Abulize; Wei-hua Pan; Nong Yu; Ya-li Yang; Hai-qing Hu; Wan-qing Liao; Shu-wen Deng (Mycopathologia, 2019)

Pterostilbene, an active component of the dragon’s blood extract, acts as an antidepressant in adult rats - Liang Yang; Yuanyuan Ran; Zhenzhen Quan; Ran Wang; Qinghu Yang; Qiutian Jia; Heao Zhang; Yanhui Li; Yiheng Peng; JianHua Liang; Hui Wang; Hiroshi Nakanishi; et al. (Psychopharmacology, 2019)

Effects of biochar and dicyandiamide combination on nitrous oxide emissions from Camellia oleifera field soil - Bang-Liang Deng; Shu-Li Wang; Xin-Tong Xu; Hua Wang; Dong-Nan Hu; Xiao-Min Guo; Qing-Hua Shi; Evan Siemann; Ling Zhang (Environmental Science and Pollution Research, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Three new species of Russula from South China - Fang Li; Qing-Li Deng (Mycological Progress, 2018)

VEGF-A regulates sFlt-1 production in trophoblasts through both Flt-1 and KDR receptors - Zhonglin Xiao; Songjun Li; Yan Yu; Mengxia Li; Jie Chen; Feng Wang; Jian Zhang; Weifen Deng; Qing Yang; Xiujun Fan (Molecular and Cellular Biochemistry, 2018)

MiR-27b promotes sheep skeletal muscle satellite cell proliferation by targeting myostatin gene - Wei Zhang; Shi-Yin Wang; Shuang-Yi Deng; Li Gao; Li-Wei Yang; Xiao-Na Liu; Guo-Qing Shi (Journal of Genetics, 2018)

A new isoflavanone from Ficus tikoua Bur - Si-Yu Zhou; Rui Wang; Li-Qing Deng; Xiao-Long Zhang; Min Chen (Natural Product Research, 2018)

The release of cytochrome c and the regulation of the programmed cell death progress in the endosperm of winter wheat (Triticum aestivum L.) under waterlogging - Yuan-Hong Qi; Fang-Fang Mao; Zhu-Qing Zhou; Dong-Cheng Liu; Min-Yu; Xiang-Yi Deng; Ji-Wei Li; Fang-Zhu Mei (Protoplasma, 2018)

HPLC-ESI-MS/MS analysis of phenolics and in vitro antioxidant activity of Epilobium angustifolium L. - Li-Qing Deng; Si-Yu Zhou; Jin-Xin Mao; Shuang Liu; Xiao-Zhong Lan; Zhi-Hua Liao; Min Chen (Natural Product Research, 2018)

Production of Humic Acid by a Bacillus megaterium Strain Using Vinasse - Nan Li; Zhi-Nian Deng; Yuan-Wen Wei; Hui-Qing Cao; Yang-Rui Li (Sugar Tech, 2018)

Phylogenetic and genetic characterization of a 2017 clinical isolate of H7N9 virus in Guangzhou, China during the fifth epidemic wave - Yongqiang Deng; Chunlin Li; Jianfeng Han; Yingfen Wen; Jian Wang; Wenxing Hong; Xiaofeng Li; Zhongyu Liu; Qing Ye; Jing Li; Changshuai Zhou; Lei Yu; et al. (Science China Life Sciences, 2017)

RETRACTED ARTICLE: Downregulation of the Long Non-Coding RNA Meg3 Promotes Angiogenesis After Ischemic Brain Injury by Activating Notch Signaling - Juan Liu; Qing Li; Kun-shan Zhang; Bin Hu; Xin Niu; Shu-min Zhou; Si-guang Li; Yu-ping Luo; Yang Wang; Zhi-feng Deng (Molecular Neurobiology, 2017)
Angiogenesis after ischemic brain injury contributes to the restoration of blood supply in the ischemic zone. Strategies to improve angiogenesis may facilitate the function recovery after stroke. Recent researches have demonstrated that dysfunction of long non-coding RNAs are associated with angiogenesis. We have previously reported that long non-coding RNAs (lncRNAs) are aberrantly expressed in ischemic stroke. However, little is known about long non-coding RNAs and theirs role in angiogenesis after stroke. In this study, we identified a rat lncRNAs, Meg3, and found that Meg3 was significantly decreased after ischemic stroke. Overexpression of Meg3 suppressed functional recovery and decreased capillary density after ischemic stroke. Downregulation of Meg3 ameliorated brain lesion and increased angiogenesis after ischemic stroke. Silencing of Meg3 resulted in a proangiogenic effect evidenced by increased endothelial cell migration, proliferation, sprouting, and tube formation. Mechanistically, we showed that Meg3 negatively regulated notch pathway both in vivo and in vitro. Inhibition of notch signaling in endothelial cells reversed the proangiogenic effect induced by Meg3 downregulation. This study revealed the function of Meg3 in ischemic stroke and elucidated its mechanism in angiogenesis after ischemic stroke.

Cloning and characterization of Agp1, the gene encoding the small subunit of ADP-glucose pyrophosphorylase from wheat and its relatives - Xiao-Wei Zhang; Qing Wang; Ling-Ling Zhang; Xiao-Juan Zhong; Qian-Tao Jiang; Jian Ma; Peng-Fei Qi; Wei Li; Guo-Yue Chen; Xiu-Jin Lan; Mei Deng; Zhen-Xiang Lu; et al. (Biologia, 2017)

Development of a stable Japanese encephalitis virus replicon cell line for antiviral screening - Qiu-Yan Zhang; Xiao-Dan Li; Si-Qing Liu; Cheng-Lin Deng; Bo Zhang; Han-Qing Ye (Archives of Virology, 2017)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

Design, synthesis and cytotoxic evaluation of a novel series of benzo[d]thiazole-2-carboxamide derivatives as potential EGFR inhibitors - Lan Zhang; Xin-Shan Deng; Chao Zhang; Guang-Peng Meng; Jiao-Feng Wu; Xue-Song Li; Qing-Chun Zhao; Chun Hu (Medicinal Chemistry Research, 2017)

Hepatoprotective triterpenoids and lignans from the stems of Schisandra pubescens - Guo-Wei Wang; Li-Qing Deng; You-Ping Luo; Zhi-Hua Liao; Min Chen (Natural Product Research, 2017)

A new diphenyl ether derivative from Mirabilis himalaica - Si-Yu Zhou; Guo-Wei Wang; Yan-Lin Zou; Li-Qing Deng; Ming-Xu Liu; Zhi-Hua Liao; Xiao-Zhong Lan; Min Chen (Natural Product Research, 2017)

Pilot Demonstration of Ceramic Membrane Ultrafiltration of Sugarcane Juice for Raw Sugar Production - Wen Li; Guo-Qing Ling; Chang-Rong Shi; Kai Li; Hai-Qin Lu; Fang-Xue Hang; Yu Zhang; Cai-Feng Xie; Deng-Jun Lu; Hong Li (Sugar Tech, 2017)

Glucocorticoids Prevent Enterovirus 71 Capsid Protein VP1 Induced Calreticulin Surface Exposure by Alleviating Neuronal ER Stress - Dan-Dan Hu; Jian-Ning Mai; Li-Ya He; Pei-Qing Li; Wen-Xiong Chen; Jian-Jiang Yan; Wei-Dong Zhu; Li Deng; Dan Wei; Di-Hui Liu; Si-Da Yang; Zhi-Bin Yao (Neurotoxicity Research, 2017)

The combination of osthole with baicalin protects mice from Staphylococcus aureus pneumonia - Shui Liu; Bowen Liu; Zhao-Qing Luo; Jiaming Qiu; Xuan Zhou; Gen Li; Bing Zhang; Xuming Deng; Zhenguo Yang; Jianfeng Wang (World Journal of Microbiology and Biotechnology, 2017)

Three new species of Boletaceae from the Heishiding Nature Reserve in Guangdong Province, China - Fang Li; Kuan Zhao; Qing-Li Deng; Ming Zhang; Christian Staehelin; Xiao-Xia Chen; Hong-Ying Chen; Geng-Shen Wang; Bing-Sheng Li (Mycological Progress, 2016)

Avian reovirus σA and σNS proteins activate the phosphatidylinositol 3-kinase-dependent Akt signalling pathway - Liji Xie; Zhixun Xie; Li Huang; Qing Fan; Sisi Luo; Jiaoling Huang; Xianwen Deng; Zhiqin Xie; Tingting Zeng; Yanfang Zhang; Sheng Wang (Archives of Virology, 2016)

Inhibitory effect of Gardenblue blueberry (Vaccinium ashei Reade) anthocyanin extracts on lipopolysaccharide-stimulated inflammatory response in RAW 264.7 cells - Wei Xu; Qing Zhou; Yong Yao; Xing Li; Jiu-liang Zhang; Guan-hua Su; Ai-ping Deng (Journal of Zhejiang University-SCIENCE B, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Micromonospora mangrovi sp. nov., isolated from mangrove soil - Qing-Yi Xie; Jian Ren; Lei Li; Yu Li; Zi-Xin Deng; Kui Hong (Antonie van Leeuwenhoek, 2016)

Eco-environmental vulnerability assessment for large drinking water resource: a case study of Qiandao Lake Area, China - Qing Gu; Jun Li; Jinsong Deng; Yi Lin; Ligang Ma; Chaofan Wu; Ke Wang; Yang Hong (Frontiers of Earth Science, 2015)

Proteomics analysis of Listeria monocytogenes ATCC 19115 in response to simultaneous triple stresses - Lei He; Qing-Li Deng; Mou-tong Chen; Qing-ping Wu; Yong-Jun Lu (Archives of Microbiology, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

Serum Aβ is Predictive for Short-Term Neurological Deficits After Acute Ischemic Stroke - Yu-Hui Liu; Hong-Yuan Cao; Ye-Ran Wang; Shu-Sheng Jiao; Xian-Le Bu; Fan Zeng; Qing-Hua Wang; Jing Li; Juan Deng; Hua-Dong Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Endostatin Combined with Platinum-Based Chemo-radiotherapy for Advanced Non-small Cell Lung Cancer - Xuan Jiang; Wei Guan; Mengxia Li; Wei Liang; Yi Qing; Nan Dai; Shiheng Zhang; Yi Deng; Hao Meng; Yuxin Yang; Zhaoyang Zhong (Cell Biochemistry and Biophysics, 2015)

Erratum to: Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Erratum to: Inhibition of Notch signaling facilitates the differentiation of human-induced pluripotent stem cells into neural stem cells - Chun-Yuan Chen; Wei Liao; Yuan-Lei Lou; Qing Li; Bin Hu; Yang Wang; Zhi-Feng Deng (Molecular and Cellular Biochemistry, 2014)

Inhibition of Notch signaling facilitates the differentiation of human-induced pluripotent stem cells into neural stem cells - Chun-Yuan Chen; Wei Liao; Yuan-Lei Lou; Qing Li; Bin Hu; Yang Wang; Zhi-Feng Deng (Molecular and Cellular Biochemistry, 2014)

Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Characterization and cross-species amplification of 11 polymorphic microsatellite loci in Liobagrus marginatoides - Xiang-Yang Jia; Ying-Wen Li; Deng-Qiang Wang; Hui-Wu Tian; Bin Tu; Da-Qing Chen (Conservation Genetics Resources, 2013)

Arabidopsis CBL-interacting protein kinase (CIPK6) is involved in plant response to salt/osmotic stress and ABA - Liang Chen; Qing-Qing Wang; Li Zhou; Feng Ren; Deng-Di Li; Xue-Bao Li (Molecular Biology Reports, 2013)

Dynamics of lamivudine-resistant hepatitis B virus strains in patients with entecavir rescue therapy - Xiao-Lin Deng; Qing-Ling Li; Jin-Jun Guo (Virus Genes, 2013)

SRPK1 contributes to malignancy of hepatocellular carcinoma through a possible mechanism involving PI3K/Akt - Bo Zhou; Yandong Li; Qing Deng; Haixiao Wang; Yuping Wang; Bing Cai; Ze-Guang Han (Molecular and Cellular Biochemistry, 2013)

Treatment with exogenous hydrogen sulfide attenuates hyperoxia-induced acute lung injury in mice - Huai-Dong Li; Zhao-Rui Zhang; Qing-Xiang Zhang; Zhi-Chu Qin; Deng-Ming He; Jin-Song Chen (European Journal of Applied Physiology, 2013)

Micromonospora avicenniae sp. nov., isolated from a root of Avicennia marina - Lei Li; You-Ju Mao; Qing-Yi Xie; Zixin Deng; Kui Hong (Antonie van Leeuwenhoek, 2013)

Cutaneous and Mucosal Phaeohyphomycosis Caused by Exophiala spinifera in a Pregnant Patient: Case Report and Literature Review - Le Wang; Xiaodong She; Guixia Lv; Yongnian Shen; Qing Cai; Rong Zeng; Caixia Li; Yiping Ge; Shuwen Deng; G. S. de Hoog; Min Li; Weida Liu (Mycopathologia, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

Landscape pattern evolution processes of alpine wetlands and their driving factors in the Zoige Plateau of China - Jun-hong Bai; Qiong-qiong Lu; Jun-jing Wang; Qing-qing Zhao; Hua Ouyang; Wei Deng; Ai-nong Li (Journal of Mountain Science, 2013)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Genetic variants of the MRC1 gene and the IFNG gene are associated with leprosy in Han Chinese from Southwest China - Dong Wang; Jia-Qi Feng; Yu-Ye Li; Deng-Feng Zhang; Xiao-An Li; Qing-Wei Li; Yong-Gang Yao (Human Genetics, 2012)

Verrucosispora wenchangensis sp. nov., isolated from mangrove soil - Qing-yi Xie; Hai-peng Lin; Lei Li; Roselyn Brown; Michael Goodfellow; Zixin Deng; Kui Hong (Antonie van Leeuwenhoek, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

C/EBP-α ameliorates CCl4-induced liver fibrosis in mice through promoting apoptosis of hepatic stellate cells with little apoptotic effect on hepatocytes in vitro and in vivo - Li-Li Tao; Yuan-Yuan Cheng; Di Ding; Shuang Mei; Jia-Wen Xu; Juan Yu; Qi Ou-Yang; Long Deng; Qi Chen; Qing-Quan Li; Zu-De Xu; Xiu-Ping Liu (Apoptosis, 2012)

Genome-wide association study identifies HMGN3 locus for spine bone size variation in Chinese - Shu-Feng Lei; Hui Shen; Tie-Lin Yang; Yan Guo; Shan-Shan Dong; Xiang-Hong Xu; Fei-Yan Deng; Qing Tian; Yong-Jun Liu; Yao-Zhong Liu; Jian Li; Hong-Wen Deng (Human Genetics, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

N-palmitoylethanolamide derivatives: synthesis and studies on anticonvulsant and antidepressant activities - Li-Ping Guan; Xin Sui; Xian-Qing Deng; Dong-Hai Zhao; You-Le Qu; Zhe-Shan Quan (Medicinal Chemistry Research, 2011)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Cell death in wheat roots induced by the powdery mildew fungus Blumeria graminis f. sp. tritici - Xiang-Yi Deng; Ji-Wei Li; Zhu-Qing Zhou; Hai-Yan Fan (Plant and Soil, 2010)

Frequent occurrence of unreduced gametes in Triticum turgidum–Aegilops tauschii hybrids - Lian-Quan Zhang; Deng-Cai Liu; You-Liang Zheng; Ze-Hong Yan; Shou-Fen Dai; Yun-Fang Li; Qi Jiang; Ya-Qing Ye; Yang Yen (Euphytica, 2010)

Inhibition of lung metastasis in mice by intravascular injection of dendritic cells and natural killer cells - Hui-fang Lv; Feng Cui; Chang-hua Yu; Li-li Deng; Jing-jing Ji; Dan Lu; Yu Yang; Wen-xiu Wang; Yu-qing Xu (Biotechnology Letters, 2009)

Genome-wide Comparisons of Gene Expression for Yield Heterosis in Maize - Bo Li; Deng-Feng Zhang; Guan-Qing Jia; Jing-Rui Dai; Shou-Cai Wang (Plant Molecular Biology Reporter, 2009)

Lactosyl derivatives function in a rat model of severe burn shock by acting as antagonists against CD11b of integrin on leukocytes - Zhihui Zhao; Qing Li; Jiale Hu; Zhongjun Li; Jinghua Liu; Aihua Liu; Peng Deng; Lin Zhang; Xiaowei Gong; Kesen Zhao; Shuangquan Zhang; Yong Jiang (Glycoconjugate Journal, 2009)

Isolation of Female-Specific AFLP Markers and Molecular Identification of Genetic Sex in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Jing Li; Si-Ping Deng; Yong-Sheng Tian; Qing-Yin Wang; Zhi-Meng Zhuang; Zhen-Xia Sha; Jian-Yong Xu (Marine Biotechnology, 2007)

Application of cDNA array for studying the gene expression profile of mature appressoria of Magnaporthe grisea - Qing-chao Jin; Hai-tao Dong; You-liang Peng; Bao-shan Chen; Jing Shao; Ye Deng; Cheng-en Dai; Yong-qi Fang; Yi-chun Lou; You-zhi Li; De-bao Li (Journal of Zhejiang University-SCIENCE B, 2007)

Reproductive biology of Alpinia blepharocalyx (Zingiberaceae): another example of flexistyly - Ling Zhang; Qing-Jun Li; Xiao-Bao Deng; Pan-Yu Ren; Jiang-Yun Gao (Plant Systematics and Evolution, 2003)